Diagnosis of Postoperative Urinary Retention Using a Simplified Ultrasound Bladder Measurement. (May 2015) - Daurat, Aurélien; Choquet, Olivier; Bringuier, Sophie; Charbit, Jonathan; Egan, Michael; Capdevila, Xavier
Abstract : BACKGROUND: In this study, we sought to determine whether a simplified ultrasound measurement of the largest transverse diameter, using a standard ultrasound machine, could be used to diagnose postoperative urinary retention (POUR). This method may replace expensive bladder volume measuring devices or a more complex ultrasound procedure (involving the measurement of 3 bladder diameters). METHODS: Patients at risk of POUR if unable to void after orthopedic surgery were evaluated in the postanesthesia care unit before discharge. Bladder diameter was first measured using a portable ultrasound device (Vscan®; GE Healthcare, Wauwatosa, WI). An automated evaluation of bladder volume was then performed (Bladderscan® BVI 3000; Diagnostic Ultrasound, Redmond, WA). Finally, when a bladder catheterization was performed, the actual urinary volume was measured. The main outcome was a bladder volume ≥600 mL as measured using the automated ultrasound scanner (Bladderscan BVI 3000) or by catheterization. Correlations between bladder volumes and diameter were studied and receiver operating characteristic curves were constructed to determine the performance in predicting a bladder volume ≥600 mL. A "gray zone" approach was developed because a single cutoff value may not always be clinically significant. RESULTS: One hundred patients were included and underwent a Bladderscan measurement. Urinary volume after catheterization was obtained in 49 patients. A significant correlation was found between the largest transverse diameter and urinary volumes assessed by the 2 methods (Bladderscan and catheterization). Pearson correlation coefficients were r = 0.80 (95% confidence interval [CI], 0.72–0.86; P < 0.001) and r = 0.79 (95% CI, 0.65–0.88; P < 0.001), respectively. The area under the receiver operating characteristic curves for the prediction of a bladder volume ≥600 mL were 0.94 (95% CI, 0.88–0.98) and 0.91 (95% CI, 0.79–0.97), respectively, for urinary volumes assessed by Bladderscan and catheterization. The optimal cutoff value was 9.7 cm for both methods. The gray zone was narrow, ranging from 9.7 to 10.7 cm thus limiting inconclusive measurements. CONCLUSIONS: A simple ultrasound measurement of the largest transverse bladder diameter seemed to be helpful to exclude or confirm POUR. Abstract : Published ahead of print January 30, 2015